(untitled) (Research, Society and Development, 2022)
This study has as its objective analyze changes in the administration of chemotherapy and endocrine therapy in breast cancer, regarding the new protocols created during the COVID-19 pandemic. A systematic literature review was performed by searching the PubMed database. Studies that analyzed the new protocols in the treatment of breast cancer and discussed their functionality were included, as well as those that observed individual interventions carried out by health professionals during the COVID-19 pandemic. The systematic search resulted in 363 articles and 41 met all the inclusion criteria, which involve keywords, stipulated time and database, and do not involve language limits. The discarded articles included case reports, content about oncological surgeries, other types of cancer and treatments, and emotional and psychosocial aspects of doctors and patients. Most studies showed adaptations in the treatment of breast cancer during the pandemic, as professionals noted the need to avoid patients going to hospitals and staying there for a long period of time, in order to prevent the contagion by Sars-CoV-2. The principle of the choices was to analyze the advantages and disadvantages of each therapy and to prefer treatments with a lower risk of infection and myelosuppression, in cases of options with similar efficacy. By exploring different experiences of each author, it is possible to note the scientific progress and discoveries that this pandemic period brought to medical society, as well as the legacy it will leave.